Clinical Features of 63 Patients with Ataxia [Características Clínicas de 63 Pacientes Con Ataxia] - Chana-Cuevas, P (Sociedad Medica de Santiago, 2018)
Background: Ataxia can be classified as genetic, sporadic or acquired. Aim: To report the clinical features of a group of patients with ataxia. Material and Methods: Review of medical records of patients consulting in a specialized center in movement disorders. Those records in which the diagnosis of “ataxia” or “ataxic syndrome” appeared, were selected for the review. Results: Of 4,282 records surveyed, the diagnosis of ataxia appeared in 95. After eliminating repeated or incomplete records, 63 were reviewed. Results: Ataxia was sporadic, genetic and acquired in 27, 22 and 14 patients, respectively. The mean age at presentation for genetic, acquired and sporadic ataxia was 24, 46 and 53 years respectively. All autosomal dominant ataxias were type 3 spinocerebellar ataxia (SCA). Friedrich’s ataxia was the most common recessive form. Most sporadic forms of ataxia were multiple system atrophy with predominant cerebellar ataxia (MSA-C) subtype. Conclusions: Considering the heterogeneity of patients with ataxia, we propose a method to approach them. © 2018, Sociedad Medica de Santiago. All rights reserved.